Continuing Reassortment Leads to the Genetic Diversity of Influenza Virus H7N9 in Guangdong, China - Lu, Jing (American Society for Microbiology, 2014)
On 30 March 2013, a novel avian influenza A H7N9 virus causing severe human respiratory infections was identified in China. Preliminary sequence analyses have shown that the virus is a reassortant of H7N9 and H9N2 avian influenza viruses. In this study, we conducted enhanced surveillance for H7N9 virus in Guangdong, China, from April to August 2013. We isolated two H7N9 viral strains from environmental samples associated with poultry markets and one from a clinical patient. Sequence analyses showed that the Guangdong H7N9 virus isolated from April to May shared high sequence similarity with other strains from eastern China. The A/Guangdong/1/2013 (H7N9) virus isolated from the Guangdong patient on 10 August 2013 was divergent from previously sequenced H7N9 viruses and more closely related to local circulating H9N2 viruses in the NS and NP genes. Phylogenetic analyses revealed that four internal genes of the A/Guangdong/1/2013 (H7N9) virus—the NS, NP, PB1, and PB2 genes—were in clusters different from those for H7N9 viruses identified previously in other provinces of China. The discovery presented here suggests that continuing reassortment led to the emergence of the A/Guangdong/1/2013 (H7N9) virus as a novel H7N9 virus in Guangdong, China, and that viral adaptation to avian and human hosts must be assessed. IMPORTANCE In this study, we isolated and characterized the avian influenza A H7N9 virus in Guangdong, China, from April to August 2013. We show that the viruses isolated from Guangdong environmental samples and chickens from April to May 2013 were highly similar to other H7N9 strains found in eastern China. The H7N9 virus isolated from the clinical patient in Guangdong in August 2013 was divergent from previously identified H7N9 viruses, with the NS and NP genes originating from recent H9N2 viruses circulating in the province. This study provides direct evidence that continuing reassortment occurred and led to the emergence of a novel H7N9 influenza virus in Guangdong, China. These results also shed light on how the H7N9 virus evolved, which is critically important for future monitoring and tracing of viral transmission.